Village Driven Development Approach in Fish Waste MSMEs Empowerment Program in Kalanganyar Village, Sedati District, Sidoarjo Regency - Kristianto Kristianto; Cyntya Sri Zuwanita (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2022)
Aquatic resources and marine products are the most significant economic potential in Kalanganyar Village. Therefore, the government and associated parties must have grave concerns about development in this area, such as local economic development with MSMEs. The village government’s position as a more democratic actor in development and crucial services for the community can also be strengthened by community empowerment, which is implemented with a village-driven development model. In this study, Pertamina DPPU Juanda’s empowerment program is based on the village-driven development strategy and uses the participatory rural appraisal (PRA) method to create MSMEs in Kalanganyar Village, is discussed. Two novel items were produced as a result of the community empowerment program, and each interest group participated actively.